Using zonal agent distribution effectively for routing in Mobile Ad Hoc Networks. (5th February 2008) - Chandrasekar, R.; Misra, Sudip
A novel routing protocol for Mobile Ad Hoc Networks (MANETs) utilising zonal distribution of mobile ant like agents is presented. The routing zones are bound together by a Mean Weighted Power Factor (MWPF) unique to each zone. Each node ensconced in a zone has the same MWPF, enabling it to form a new zone on discovery of a different power factor broadcast from its local neighbourhood.